THE EFFECT OF USING WHATSAPP MESSENGER ON STUDENTSâ€™ SPEAKING ACHIEVEMENT AT THE SECOND GRADE STUDENTS OF MADRASAH ALIYAH NEGERI (MAN) 1 KENDARI - Ahmad, Aras Nur (Journal of Teaching of English, 2019)
The use of technology in teaching and learning is an important aspect which has receivedÂ  considerable attentionÂ  inÂ  recent Â years. Â In a similar Â sense, Â the use of mobile phone application especially WhatsApp Â messenger to Â increase effectiveness of instruction has been acknowledged through a number of studies carried out so far. This study was conducted to find the effect of using WhatsApp Messenger on studentsâ€™ speaking achievement at the second grade students of Madrasah Aliyah Negeri (MAN) 1 Kendari. The research question is that â€œIs there any significant effect of using WhatsApp messenger on studentsâ€™ speaking achievement at the second grade students of Madrasah Aliyah Negeri (MAN) 1 Kendari?â€ This study used a quantitative approach by applying a comparative study. The participants of the study consisted of 60 students who were in two different classes: class XI IPA 2 as the experimental class and class XI IPA 4 as the control class. The experimental class consisted of 30 students taught in a combination method (WhatsApp Messenger and discussion method)Â  Â while the control class consisted of 30 students taught through using a conventional method. The Â results of thisÂ  study showedÂ  thatÂ  there Â were Â differences Â in Â the Â speaking achievement of the students in the experimental class and the control class. This difference was in favor of the experimental class. The value of Chi-Square count is 28.486 and the Chi-Square Table is 19.675. So the H1 accepted and H0 is rejected . The differences between the two classes indicated that integrating the WhatsApp application in teaching English language improved speaking achievement of the students of the experimental class.Â Keywords: WhatsApp Messenger, Discussion, Speaking Â achievement.